Katolicko-prawosławne spory o celibat w XVI-wiecznej Rzeczypospolitej .......... 53 - Nowak, Alicja Z. (Tożsamość i pamięć : konteksty kulturowe i społeczne. Studia ukrainoznawcze, 2021)
CATHOLIC-ORTHODOX DISPUTES OVER CELIBACY IN THE 16TH CENTURY POLAND Celibacy of the clergy was one of the subjects raised in the 16th-century religious polemic in the Polish- Lithuanian Commonwealth in connection with the emergence of Protestantism, which rejected the clergy’s unmarried state and the wave of discussions devoted to this problem during the Council of Trent (1545-1563). Initially, the main discussants were Roman Catholic opponents and supporters of celibacy (Andrzej Frycz Modrzewski, Stanisław Orzechowski vs Jan Dziaduski, Stanisław Hozjusz). A little later – the famous Counter-Reformation defenders of celibacy (Piotr Skarga) and Orthodox writers (Herasym Smotrycki, Wasyl Surażski, Melecjusz Pigas) supported by Protestants (Marcin Broniewski), who defended the right of the clergy to have wives. At the turn of the 16th and 17th centuries, the first and ambiguous voices of representatives of the Uniate Church appeared (Hipacy Pociej), which did not accept the notion of the clergy’s celibacy.